2000
DOI: 10.1136/jnnp.69.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic coherence analysis in multiple sclerosis: correlation with clinical, neuropsychological, and MRI findings

Abstract: Band coherence was decreased between homologous areas (p<0.02). Band coherence was decreased both in the local and long distance connections (p<0.0005). These findings were most striking both in patients with high MRI subcortical lesion load and in patients with cognitive involvement. A significant correlation was found between interhemispheric (p=0.02) and (p=0.017) and anteroposterior (p=0.013) coherence and subcortical MRI lesion load, but not with exclusively periventricular lesion load. Conclusions-These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
75
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 53 publications
12
75
0
3
Order By: Relevance
“…Furthermore, these results are in line with previous evidence showing that lesions of the white matter in VaD were directly related to a widespread slowing of EEG rhythmicity (Szelies et al, 1992(Szelies et al, , 1999. The white matter lesions of multiple sclerosis also decreased the frequency of the alpha rhythm (Leocani et al, 2000), while successful immunosuppressive treatment, probably restoring appropriate nerve propagation, resulted in recovery of normal alpha frequency without effects on the relative power (Colon et al, 1981). Finally, tumors of the cerebral white matter, but not of the gray matter, decrease the frequency of the alpha rhythm (Gloor et al, 1968;Goldensohn, 1979).…”
Section: Relative Power and Frequency Of Alpha Rhythms In Mild Dementiasupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, these results are in line with previous evidence showing that lesions of the white matter in VaD were directly related to a widespread slowing of EEG rhythmicity (Szelies et al, 1992(Szelies et al, , 1999. The white matter lesions of multiple sclerosis also decreased the frequency of the alpha rhythm (Leocani et al, 2000), while successful immunosuppressive treatment, probably restoring appropriate nerve propagation, resulted in recovery of normal alpha frequency without effects on the relative power (Colon et al, 1981). Finally, tumors of the cerebral white matter, but not of the gray matter, decrease the frequency of the alpha rhythm (Gloor et al, 1968;Goldensohn, 1979).…”
Section: Relative Power and Frequency Of Alpha Rhythms In Mild Dementiasupporting
confidence: 92%
“…Accordingly, these cholinergic inputs would sustain the power of the alpha rhythm (Holschneider et al, 1998;Villa et al, 2000). This explanation agrees with the reduction of functional cortico-cortical coupling, revealed by EEG coherence studies, in AD patients compared to normal controls (Leocani et al, 2000) and VaD patients (Leuchter et al, 1992). The regulation of the alpha frequency would otherwise be relatively independent of the full integrity of the cholinergic systems and corticocortical connections (mainly impaired in mild AD).…”
Section: Relative Power and Frequency Of Alpha Rhythms In Mild Dementiasupporting
confidence: 80%
“…In fact, a theoretical model considering a mean speed propagation in white matter fibers of 7.5 m/s (together with other parameters) is associated with a fundamental mode frequency of 9 Hz (Nunez, 1995;Nunez and Srinivasan, 2006), that is, the typical mode of scalp-recorded EEG. It is to be noted that a correlation between white matter damage and widespread slowing of EEG rhythmicity was found in other studies, following the presence of cognitive decline (d'Onofrio et al, 1996;Szelies et al, 1992Szelies et al, , 1999, multiple sclerosis (Leocani et al, 2000), or cerebral tumors (Gloor et al, 1977;Goldensohn, 1979). In the present study, we found neither impact of vascular damage on the IAF, nor significant correlation between CV damage score and IAF.…”
Section: Eeg Frequency Indices Of a Rhythms And CV Damagementioning
confidence: 61%
“…This pattern of dysfunctions resembles that typical of subcortical dementia and is considered as mostly dependent on the disruption of connections between cortical associative areas, related to demyelination and/or axonal loss within the white matter immediately underlying the cortex [39].…”
Section: Introductionmentioning
confidence: 76%